A COMPARATIVE STUDY OF TRADITIONAL VS. SOCIAL MEDIA-BASED APPROACHES IN VOCABULARY ACQUISITION (Journal of Uzbekistan’s Development and Research, 2025)
This study explores the effectiveness of traditional versus social media-based methods in vocabulary acquisition among EFL learners. Drawing on previous research, it compares how learners engage with vocabulary through conventional classroom techniques and modern digital platforms. The findings suggest that social media-based learning fosters better retention, motivation, and contextual usage due to its interactive and authentic environment. While traditional methods provide structure and depth, social media encourages active participation and real-life application. The study highlights the importance of integrating both approaches to create a balanced and effective vocabulary learning experience.